Storytelling Poetry in the Poems of ‘Alī ibn al-Jahm and the Ode of the Creation of Adam - Tayebeh Seifi; Zahra Mirzaei Hotkani; Masoumeh Seifuri (Al-Ma‘rifah, 2022)
Story poetry as a branch of the big tree of poetry and literature in Abbasid era, is one of the important tools for discovering historical facts. This study showed that ‘Alī ibn al-Jahm can be considered one of the pioneers of this literary art in the Abbasid era. He paved the way for poets to depict history in this format and create novel works in this era and immortalize those historical events. By analyzing each element of the story in ‘Alī ibn al-Jahm’s chapter “Creation of Adam”, this study has proved that this work is a story poem and also tries to determine the poet’s goals from the order of this work for the audience. The results of this study show that the aim of ‘Alī ibn al-Jahm in this poem is to teach the teachings of Islam to the audience and people of his time in addition to retelling the events and history of the prophets. Considering that ‘Alī ibn al-Jahm was a court poet and praiser of the caliphs of Banī ‘Abbās, probably the aim of the poet is also to teach a lesson from the caliphs and also the behavior of the prophets and the ancients.